Emotional attachments in children's toy design dimensions and strategies: a grounded theory approach - Hong, Yao; Alli, Hassan; Shaari, Nazlina (Raiya Academic International, 2024)
Children's emotional attachments to toys foster trust and stability, impacting psychological growth. This study evaluates the concept of emotional attachments in children's toy designs. Employing a grounded theory methodology, it seeks to establish a conceptual framework for understanding the elements and principles of emotional attachments in toys. By shedding light on the factors that develop children’s emotional attachments with their toys, this research aims to inform the design and development processes of toys that promote healthy emotional development. The findings suggest that integrating a conceptual model of emotional attachments into the design processes can lead to the creation of toys that facilitate children's holistic growth and offer them positive experiences of emotional connection. Furthermore, the study proposes a conceptual framework for integrating emotional attachment into children's toy design and development processes. This has profound implications for toy designers, teachers, manufacturers, and education researchers aiming to enhance children's emotional well-being through play. © 2024, Raiya Academic International LLC. All rights reserved.